2020
DOI: 10.1038/s41379-019-0391-9
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter analysis of genomic profiles and PD-L1 expression of primary lymphoepithelioma-like carcinoma of the lung

Abstract: To understand the molecular mechanism of tumorigenesis of pulmonary lymphoepithelioma-like carcinoma and explore potential therapeutic strategies, we investigated the genomic profiles and PD-L1 expression of 29 Chinese pulmonary lymphoepithelioma-like carcinoma patients at various stages. We performed capture-based targeted sequencing on tissue samples collected from 27 patients with sufficient samples using a panel consisting of 520 cancer-related genes, spanning 1.64 Mb of the human genome. We identified 184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 56 publications
12
43
0
Order By: Relevance
“…In this study, 79% of pulmonary LELC were positive with PD-L1 at TPS ≥ 1% by the assessment of PD-L1 IHC 22C3. The result was consistent with previous findings of 66-76% of pulmonary LELC patients positive for PD-L1, with the threshold of 5% positively stained tumor cells [6,9,34]. Among case reports of primary pulmonary LELC patients treated with PD-1 inhibitors, two partial responses were noted, and five patients had stable disease [9,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, 79% of pulmonary LELC were positive with PD-L1 at TPS ≥ 1% by the assessment of PD-L1 IHC 22C3. The result was consistent with previous findings of 66-76% of pulmonary LELC patients positive for PD-L1, with the threshold of 5% positively stained tumor cells [6,9,34]. Among case reports of primary pulmonary LELC patients treated with PD-1 inhibitors, two partial responses were noted, and five patients had stable disease [9,[35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of a distinct genomic background provided insight into how the genetics of pulmonary LELC varied from other NSCLC subtypes. In concordance with previous studies, pulmonary LELC showed a low degree of somatic mutation rate [9,10]. Its median mutation rate was 0.9 and 1.7 mutations per Mb by whole genome sequencing (78×) and targeted sequencing (907×), respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, the relationship between PD-L1 expression and gene mutations of lung was also arouse concern in recent studies [25,44,45]. Unlike other NSCLC subtypes, PPLELC patients showed lower mutation rates of some common gene, such as ALK, KRAS and EGFR [25,44,45]. The explanation for this may be that there had a unique gene profile in LELC of lung [45].…”
Section: Plos Onementioning
confidence: 99%
“…The copy number cut-off of 1.5 corresponds to copy number deletion and 2.64 for copy number amplifications 21 . Variants were filtered using the VarScan fpfilter pipeline, and loci with depth less than 100 were filtered out 38 . DNA translocation analysis was performed using Tophat2 and Factera1.4.3.…”
Section: Methodsmentioning
confidence: 99%